THE PROBLEM OF STUDYING ETHNOECOLOGICAL CULTURE BASED ON THE SOCIO-GEOGRAPHICAL APPROACH (Scientific journal of the Fergana State University, 2024)
The article expresses an opinion about the culture of rational use of the disappearing nature of local peoples in recent years. It is revealed that the system of interrelations and relations of nature and society in the modern period has fallen into a very difficult situation, and the main method of nature conservation in this situation is the use of a program-target type in the landscape-ethno-economic system. It is also substantiated that the preservation of a high ethnoecological culture formed over centuries, and enriching it with innovative ideas, carrying out practical work through the implementation of landscape-ecological planning is the most reasonable way to protect nature.